1997
DOI: 10.1128/iai.65.6.2060-2066.1997
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica serotype O:3 alters the expression of serologic HLA-B27 epitopes on human monocytes

Abstract: The expression of serologic HLA-B27 epitopes on leukocytes of patients with reactive arthritis or ankylosing spondylitis has been shown to be modified in the course of the disease. The purpose of this work was to study whether phagocytosis of arthritis-triggering microbes in vitro alters the expression of HLA-B27 molecules on human antigen-presenting cells and to characterize the underlying mechanisms. Human monocytes and HLA-B27-or HLA-A2-transfected human U-937 cells were exposed to Yersinia enterocolitica s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…A recent study has shown altered expression of serologic HLA-B27 epitopes on human monocytes following exposure to Yersinia or invasion by Salmonella enteritidis, although in contrast with our data, ME1 epitope expression was decreased (33). This could reflect differences in signal transduction and/or antigen processing associated with bacterial invasion.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study has shown altered expression of serologic HLA-B27 epitopes on human monocytes following exposure to Yersinia or invasion by Salmonella enteritidis, although in contrast with our data, ME1 epitope expression was decreased (33). This could reflect differences in signal transduction and/or antigen processing associated with bacterial invasion.…”
Section: Discussioncontrasting
confidence: 99%
“…HLA-B27-and HLA-B7-transfected L cells had stable and comparable cell surface expression of the transfected genes when stained with specific MAbs. Furthermore, the expression level of these transfected genes appeared to be optimal, since it was similar to those of endogenous HLA-B27 and HLA-B7 on human cells (19,34). The expression of human and murine MHC I antigens on the transfectants is shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…As negative controls, isotype-matched mouse MAbs were used. The cells were stained by the indirect immunofluorescence technique by a protocol described earlier (34). Cell surface expression was analyzed by flow cytometry (FACScan; Becton Dickinson, San Jose, Calif.).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial products such as lipopolysaccharide may also be detected inside ReA synovial membranes and fluid (9). Various effects of bacterial infection on HLA-B27 biosynthesis and expression have been reported: a decrease in the synthesis of HLA-B27 molecules has been described for Yersinia enterocolitica-infected human monocytes (44), and Salmonella or Yersinia infection may induce alternative splicing of HLA-B27 mRNA, leading to a soluble form of the molecule (12). In our conditions, S. flexneri infection did not affect the expression level of HLA-B27 molecules.…”
Section: Discussionmentioning
confidence: 99%